Jump! - Cooper, Jilly (London Bantam Press, 2010)
Etta Bancroft - sweet, kind, still beautiful - adores racing and harbours a crush on one of its stars, the handsome, high-handed owner-trainer Rupert Campbell-Black. When her bullying husband dies, Etta's selfish, ambitious children drag her from her lovely Dorset home to live in a hideous modern bungalow in the Cotswold village of Willowwood
Keywords: Race horses -- Racehorse trainers -- Widows